Intelligent image and video interpretation algorithms and applications - Tian, Jing, 1979-; Chen, Li, 1977- (Information Science Reference, 2013)
"This book covers all aspects of image and video analysis from low-level early visions to high-level recognition, highlighting how these techniques have become applicable and will prove to be a valuable tool for researchers, professionals, and graduate students working or studying the fields of imaging and video processing"--Resumé vydavatele
Keywords: digitální zpracování obrazu; počítačové zpracování obrazu; počítačová analýza obrazu; počítačové zpracování zvuku; digitální videozáznam; umělá inteligence; algoritmy; digital image processing; computer image processing; computer image analysis; computer sound processing; digital video recording; artificial intelligence; algorithms; sborníky; elektronické knihy; papers of several authors; electronic books